2018
DOI: 10.1136/bmjopen-2017-019443
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple barriers to participation for people with psychosocial disability in Dehradun district, North India: a cross-sectional study

Abstract: ObjectivesThis study used a population-based cross-sectional survey to describe the prevalence of psychosocial disability and unmet need for access to services in North India.SettingThis study was conducted in Dehradun district, Uttarakhand, in 2014.ParticipantsA population-based sample of 2441 people over the age of 18 years.Primary outcome measuresThe Rapid Assessment of Disability survey tool identified people with disability and used an adapted version of the Kessler scale to identify those with psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…We identified three key community groups: widows who are disadvantaged due to their gender, their risk of lower socioeconomic status and the stigmatising influences of widowhood [25,26]. People with psychosocial disability (PPSD) residing in informal urban communities are disadvantaged by low socioeconomic status, the negative public perceptions and reduced access to services linked to the area where they live, and their stigmatising experiences of exclusion [27,28] and thirdly, people with disabilities in rural areas who are disadvantaged by lack of access to services related to where they live, and by systemic structural exclusion with multiple barriers to participation [29,30]. In describing the mental distress and coping strategies used by participants we aimed to consider the impacts of intersecting axes of disadvantage using an intersectional lens [31].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…We identified three key community groups: widows who are disadvantaged due to their gender, their risk of lower socioeconomic status and the stigmatising influences of widowhood [25,26]. People with psychosocial disability (PPSD) residing in informal urban communities are disadvantaged by low socioeconomic status, the negative public perceptions and reduced access to services linked to the area where they live, and their stigmatising experiences of exclusion [27,28] and thirdly, people with disabilities in rural areas who are disadvantaged by lack of access to services related to where they live, and by systemic structural exclusion with multiple barriers to participation [29,30]. In describing the mental distress and coping strategies used by participants we aimed to consider the impacts of intersecting axes of disadvantage using an intersectional lens [31].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A systematic review published in 2016 identified only one previous example; it came from Brazil, an upper-middle income country, and users were not involved until data had already been collected [68, 69]. A 2017 survey on psychosocial disabilities and barriers to participation in North India may have involved data collectors with psychosocial disabilities, although this is unclear from the study’s text [67, 70]. While engagement of M&E Buddies in data collection is desirable from an inclusion perspective, and may be more sustainable than relying on external evaluators, the use of M&E Buddies has not yet been tested in this context.…”
Section: Discussionmentioning
confidence: 99%
“…15 Differences in male and female patient experience for schizophrenia have been documented in India. 1 Stigma is not only to blame as a complete lack of realization that mental health problems are real health problems is also part of rural understanding in parts of India. 16 This is not seen only in the general public, even health care professionals are known to exhibit negative attitudes toward mental health patients and a systematic evaluation of health care professional attitudes is much needed for better policy formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness and community participation are vital to reduce the mental health burden. In India, focused studies show a direct link between community participation and mental health, 1 indicating that wealth and longevity are significantly lower for people with mental health ailments. Stigma and discrimination against mental health patients is common, more so for women than men and the stigma is not just a rural phenomenan.…”
Section: Introductionmentioning
confidence: 99%